Transfection With Plasmid Causing Stable Expression of a Foreign Gene Affects General Proteome Pattern in Giardia lamblia Trophozoites - Heller, Manfred; Braga, Sophie; Müller, Norbert; Müller, Joachim (Frontiers in Cellular and Infection Microbiology, 2020)
Giardia lamblia is an important causative agent of persistent diarrhea in humans, domestic animals, and cattle. Basic research is usually performed with the strain WBC6 and includes genetic manipulations such as transfections. Here, we investigate how transfection with a plasmid causing stable expression of a foreign gene affects the whole proteome pattern. Using shotgun mass spectrometry, we compare the proteomes of untransfected trophozoites to trophozoites transfected with Escherichia coli glucuronidase A (GusA). Besides GusA, which is detected in the transfected trophozoites only, the proteomes of untransfected and transfected trophozoites differ by 132 differentially expressed proteins. In particular, transfection induces antigenic variation. Since transfection causing stable expression affects the proteome pattern, transfection experiments should take into account this effect. Due to a unique peptide panel, GusA is an example for a suitable internal standard for experiments involving transfected cells. Data are available via ProteomeXchange with identifier PXD022565.